DEVELOPING A RELIGIOUS MODERATION-BASED CURRICULUM MODULE FOR LABORATORY MADRASAH TSANAWIYAH IN ISLAMIC HIGHER EDUCATION - Kosim, Muhammad; Kustati, Martin; Sirait, Wahida Raihan; Fajri, Suryadi; Febriani, Suci Ramadhanti; Mufti, Mufti; Perrodin, David D (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2024)
Religious moderation is a key element in fostering tolerance and harmony in a diverse society, and its integration into Islamic education is crucial for achieving these goals. This study aimed to develop a curriculum model based on religious moderation for madrasas, utilizing the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) to ensure its comprehensive integration. The research involved identifying existing practices at MTs Pembangunan UIN Jakarta, designing a curriculum model incorporating religious moderation into intracurricular, extracurricular, co-curricular, and madrasa culture activities, and piloting the developed module. The results revealed that while MTs Pembangunan UIN Jakarta did not explicitly implement religious moderation in its character and moral development programs, the school exhibited implicit practices aligned with these values. The curriculum developed in this study was assessed as highly valid in terms of content, presentation, graphics, and language, with a particular focus on its practical implementation in fostering students’ attitudes toward religious moderation. The findings emphasize the importance of a multi-faceted approach to embedding religious moderation in all aspects of madrasa life. This study provides valuable insights into how curriculum design can be an effective tool for promoting religious moderation, with implications for improving Islamic education by integrating these values into both formal and informal educational settings.